Neuropeptide and Small Transmitter Coexistence: Fundamental Studies and Relevance to Mental Illness - Hökfelt, Tomas; Barde, Swapnali; Xu, Zhi-Qing David; Kuteeva, Eugenia; Rüegg, Joelle; Le Maitre, Erwan; Risling, Mårten; Kehr, Jan; Ihnatko, Robert; Theodorsson, Elvar; Palkovits, Miklos; Deakin, William; et al. (Frontiers in Neural Circuits, 2018)
Neuropeptide are auxiliary messenger molecules that always co-exist in nerve cells with one or more small-molecule (classic) neurotransmitters. Neuropeptides act both as transmitters and trophic factors, and play a role especially when the nervous system is challenged, as by injury, pain or stress. Here neuropeptides and coexistence in mammals are reviewed, but with special focus on the 29/30 amino acid galanin and its three receptors GalR1, -R2 and -R3.  In particular, galanin’s role as a co-transmitter in both rodent and human noradrenergic locus coeruleus (LC) neurons is addressed. Extensive experimental animal data strongly suggest a role for the galanin system in depression–like behavior. The translational potential of these results was tested by studying the galanin system in human postmortem brains, first normal brains, and then by comparing five regions of brains obtained from depressed people who committed suicide, and from matched controls. It is hypothesized that, when exposed to severe stress, the noradrenergic LC neurons fire in bursts and release galanin from their soma/dendrites. Galanin then acts on somato-dendritic, inhibitory GalR3 autoreceptors, opening potassium channels and inhibiting firing. The purpose of these autoreceptors is to act as a ‘brake’ to prevent overexcitation, a brake that also is part of resilience to stress that protects against depression. Depression then arises when the inhibition is too strong and long lasting - a maladaption, allostatic load, leading to depletion of NA levels in the forebrain. It is suggested that disinhibition by a galanin GalR3 antagonist may have antidepressant activity by restituting forebrain NA levels. A role of galanin in depression is also supported by a recent candidate gene study, showing that variants in genes for galanin and its three receptors confer increased risk of depression and anxiety in people who experienced childhood adversity or recent negative life events. Taken together, the neuropeptide galanin, coexisting in LC neurons, may participate in the mechanism underlying resilience against a serious and common disorder, MDD. These results may lead to an increased understanding of how this illness develops which in turn can provide a basis for its treatment.